2014
DOI: 10.1360/012014-53
|View full text |Cite
|
Sign up to set email alerts
|

Hankel determinants of the Cantor sequence

Abstract: Let τ be the substitution 1 → 101 and 0 → 1 on the alphabet {0, 1}. The fixed point of τ leading by 1, denoted by s, is a Sturmian sequence. We first give a characterization of s using f-representation. Then we show that the distribution of zeros in the determinants induces a partition of integer lattices in the first quadrant. Combining those properties, we give the explicit values of the Hankel determinants Hm,n of s for all m ≥ 0 and n ≥ 1. Contents 1. Introduction 1 2. Some properties of the sequence s 3 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Using Bugeaud's method, in 2012, Coons [12] proved that the irrationality exponent of the sum of the reciprocals of the Fermat numbers is 2. Recently, Wen and Wu [23] showed that the irrationality exponents of the Cantor real numbers are exactly 2 in the same way.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Using Bugeaud's method, in 2012, Coons [12] proved that the irrationality exponent of the sum of the reciprocals of the Fermat numbers is 2. Recently, Wen and Wu [23] showed that the irrationality exponents of the Cantor real numbers are exactly 2 in the same way.…”
Section: Introductionmentioning
confidence: 87%
“…In 2012, with the help of C++ program, Coons and Vrbik [11] showed that the Hankel determinant H n (F ) = 0 of the regular paperfolding sequence for n ≤ 2 13 + 3. In 2013, Wen and Wu [23] investigated the Hankel determinants of the Cantor sequence which is the fixed point of the endomorphism θ : 1 → 101, 0 → 000. They also proved that the Hankel determinants of the Thue-Morse sequence are all nonzero.…”
Section: 2mentioning
confidence: 99%